The effects of prescription drug monitoring programs on labor market activity and credit outcomes - Sumedha Gupta; Bhashkar Mazumder (Federal Reserve Bank of Chicago, 2023)
We examine how the availability of prescription opioids affects labor market activity and household economic well-being. While greater access to opioids may lead people to substance use disorders and negative economic consequences, appropriate pain medication may allow some individuals to effectively participate in the labor market. We study prescription drug monitoring programs (PDMPs), which were designed to curb inappropriate opioid prescribing and assess how these policies affected labor force attachment and credit outcomes. We use variation across states in the timing of implementation of PDMPs and recent methods developed for difference-in-difference event study designs with multiple time periods. In line with previous work, we find that PDMPs lead to a decline in opioid prescribing rates. Although we find that these reductions in opioid supply have no clear effect on measures of labor force activity in our pooled sample, we see some suggestive evidence of negative effects on labor force attachment in states where there is less scope for substitution to illicit drugs. We also show that PDMPs lead to a decline in credit scores and increases in the number and amount of third-party debt collections, and that these effects are more pronounced in states lacking an illicit market. These findings suggest that some individuals are likely negatively affected by the lack of access to pain medication due to the PDMP laws.
Keywords: 330; Opioids; prescription drug monitoring programs; labor force participation; disability insurance; collections; credit scores